2022
DOI: 10.1097/dcr.0000000000002553
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Pouch and Para-Pouch Inflammatory and Neoplastic Disorders

Abstract: BACKGROUND:Restorative proctocolectomy with ileal pouch-anal anastomosis (IPAA) is used to treat patients with ulcerative colitis or familial adenomatous polyposis who need colectomy. While this procedure substantially improves patient's quality of life and reduces cancer risk, it is associated with a variety of sequelae‚ including surgical complications, inflammatory disorders, and neoplasia. Pouchitis, cuffitis, and Crohn's disease of the pouch are the most common inflammatory disorders of the pouch and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…3), or functional pouch disorders. [15][16][17] In addition, cross-sectional imaging may play a key role in the evaluation of fistulas or other penetrating complications of Crohn's disease. 5 Pouch inflammation is commonly summarized quantitatively through the pouch disease activity index (PDAI) and the modified PDAI (mPDAI).…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…3), or functional pouch disorders. [15][16][17] In addition, cross-sectional imaging may play a key role in the evaluation of fistulas or other penetrating complications of Crohn's disease. 5 Pouch inflammation is commonly summarized quantitatively through the pouch disease activity index (PDAI) and the modified PDAI (mPDAI).…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…33,34 Routine surveillance pouchoscopy with segmental biopsy, particularly image-enhanced endoscopy, is recommended for these patients. [35][36][37][38] Oral Budesonide Oral budesonide with or without concurrent immunomodulators or ursodeoxycholic acid (UDCA) has been described to treat IgG4-associated sclerosing cholangitis 39 or PSC 40 with minimum or no efficacy. In contrast, a double-blinded, double-dummy, controlled trial of budesonide enema and oral metronidazole in 26 patients with pouchitis showed comparative efficacy as measured by the Pouchitis Disease Activity Index.…”
Section: S109mentioning
confidence: 99%
“…33,34 Routine surveillance pouchoscopy with segmental biopsy, particularly image-enhanced endoscopy, is recommended for these patients. 35–38…”
Section: Psc and The Pouchmentioning
confidence: 99%
“…A biopsy should be taken from the suture lines or staple lines because foreign body-associated granulomas may be mistaken for noncaseating granulomas. 58…”
Section: S60mentioning
confidence: 99%
“…Although pouchoscopy may be performed for the insertion of a decompression tube, most patients require surgical intervention. 58…”
Section: Pouch Bodymentioning
confidence: 99%